Risk of ovarian hyperstimulation syndrome in women with malignancies undergoing treatment with long-acting gonadotropin-releasing hormone agonist after controlled ovarian hyperstimulation for fertility preservation: a systematic review - Caroline Ingold; Paula Andrea Navarro; Renato de Oliveira; Caio Parente Barbosa; Giuliano Bedoschi (SAGE Publishing, 2023)
Background: Fertility preservation is an important quality of life issue for women of reproductive age undergoing gonadotoxic treatment. The possibility of administering an adjuvant long-acting gonadotropin-releasing hormone agonist (GnRHa) with the aim of reducing the number of follicles susceptible to the effects of chemotherapy and thus reducing the risk of ovarian damage is considered in some international society guidelines, particularly in certain cancers such as breast cancer. Nowadays, the administration of long-acting GnRHa after controlled ovarian hyperstimulation (COH) for fertility preservation by cryopreservation of oocytes or embryos is increasingly used. However, cases of ovarian hyperstimulation syndrome (OHSS) have been reported following the use of long-acting GnRHa after COH for fertility preservation, indicating that the potential adverse effects of this treatment need to be further investigated. Objectives: The aim of this systematic review was to comprehensively characterize patients who developed OHSS after treatment with long-acting GnRHa following COH for fertility preservation. Methods: A comprehensive search of major electronic databases through January 2023 was performed. Studies reporting the use of long-acting GnRHa after COH for fertility preservation and the development of OHSS were included. Risk of bias was assessed using a modified version of the Newcastle-Ottawa scale. Results were synthesized qualitatively. Results: Three studies with five patients met the eligibility criteria. The majority of patients were diagnosed with breast cancer and all patients underwent COH for oocyte cryopreservation. OHSS occurred in all patients after administration of long-acting GnRHa. The interval between ovulation induction and administration of long-acting GnRHa thereafter ranged from 3 to 5 days. All patients were treated conservatively and recovered without complications. Conclusion: Current evidence suggests that the use of long-acting GnRHa after COH for fertility preservation may be associated with OHSS. Healthcare providers should thoroughly discuss the benefits and risks of this intervention with their patients before making a decision. Further studies are needed to fully elucidate the causal relationship between long-acting GnRHa and OHSS in this population.